Fluid-structure interaction for water hammers effects in petroleum and nuclear plants - Messahel, R; Cohen, B; Souli, M; Moatammedi, M (The International Journal of Multiphysics, 2011)
Fluid-Structure Interaction (FSI) becomes more and more the focus of computational engineering in Petroleum and Nuclear Industry in the last years. These problems are computer time consuming and require new stable and accurate coupling algorithms to be solved. For the last decades, the new development of coupling algorithms, and the increasing of computer performance have allowed to solve some of these problems and some more physical applications that has not been accessible in the past; in the future this trend is supposed to continue to take into account more realistic problem. In this presentation, numerical simulation using FSI capabilities in LS-DYNA, of hydrodynamic ram pressure effect occurring in nuclear industry is presented.